2017
DOI: 10.1158/1541-7786.mcr-16-0243-t
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Outcomes for HER2-enriched Cancer Using Growth and Metastasis Signatures Driven By SPARC

Abstract: Understanding the mechanism of metastatic dissemination is crucial for the rational design of novel therapeutics. The secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein which has been extensively associated with human breast cancer aggressiveness although the underlying mechanisms are still unclear. Here, shRNA-mediated SPARC knockdown greatly reduced primary tumor growth and completely abolished lung colonization of murine 4T1 and LM3 breast malignant cells implanted in synge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 47 publications
3
27
0
2
Order By: Relevance
“…Another study suggested that the Ala variant increased the risk of lung cancer, indicating that it may promote ERBB2 activity 25 . However, Minn et al 26 and Guttlein et al 27 showed that, in ERBB2 overexpressing breast cancer cell lines, lung colonization is predominant and mediated by SPARC (secreted protein acidic and rich in cysteine).…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that the Ala variant increased the risk of lung cancer, indicating that it may promote ERBB2 activity 25 . However, Minn et al 26 and Guttlein et al 27 showed that, in ERBB2 overexpressing breast cancer cell lines, lung colonization is predominant and mediated by SPARC (secreted protein acidic and rich in cysteine).…”
Section: Discussionmentioning
confidence: 99%
“…A similar ECM gene cluster, comprising COL1A1, FN1, LOX, SPARC, TIMP3, and COL1A2 has been associated with the resistance to tamoxifen when administered as a first-line therapy inpatients with metastatic breast cancer [11]. More recently, a SPARC-driven gene expression signature obtained from murine models predicted the clinical outcome of patients with HER2-enriched breast cancer subtypes [12]. Notably, signatures enriched in collagen genes together with LOX, THBS2, TIMP3, and SPARC have also been associated with poor survival after adjuvant chemotherapy and with a high hazard of death in ovarian cancer [13,14].…”
Section: Relevance Of the Extracellular Matrix In Tumorsmentioning
confidence: 99%
“…These include cytokines, growth factors, ligands, small RNAs, DNA, soluble factors, metabolite, and the non-cellular solid-state extracellular matrix (ECM) that make the TME more amiable for the progression of the tumor. 8,42,52,72,92,99,101 The cellular interactions with the non-cellular microenvironment also play a role in governing the tumor metastasis. 23 Tumor-stromal cell crosstalk intensifies the production of chemokines, growth factors, cytokines, matrix metalloproteinases (MMPs) which facilitate the tumor growth and angiogenesis.…”
Section: Genetic Heterogeneitymentioning
confidence: 99%
“…Among a class of matricellular proteins in TEM, a secreted protein acidic and rich in cysteine (SPARC) has been shown to be linked to aggressiveness of human breast cancer. G€ uttlein et al 42 revealed the clinical evidence of SPARC in breast carcinoma and highlighted its importance in therapeutics and biomarker study. Recently, Hu et al 49 showed the presence of several secreted proteins, namely SULT2B1, CEACAM5, SPRR3, AGR2, S100P, and S100A14, which can potentially be used as therapeutic targets and biomarkers in non-small cell lung cancer (NSCLC).…”
Section: Matricellular Proteins As Components Of Ecmmentioning
confidence: 99%